The relationship between dynamic balance, jumping ability, and agility with 100 m sprinting performance in athletes with intellectual disabilities - Jouira, G.; Alexe, D. I.; Tohanean, D. I.; Alexe, C. I.; Tomozei, R. A.; Sahli, S. (Sports, 2024)
Sprinting is a competitive event in athletics that requires a combination of speed, power, agility, and balance. This study investigated the relationship between dynamic balance, jumping ability, and agility with 100 m sprinting performance in athletes with intellectual disabilities, addressing an underexplored connection. A sample of 27 sprinters with intellectual disabilities participated in this study and completed 100 m sprint and various tests, including the Y Balance Test (YBT), the Crossover hop test, squat jump (SJ), countermovement jump (CMJ), and t-test to evaluate their dynamic balance, jumping ability, and agility, respectively. The findings revealed significant negative correlations between the YBT, Crossover hop test, SJ, and CMJ and 100 m sprint performance (r range: -0.41 to -0.79, p < 0.05). Regression analysis identified these variables as significant predictors (R2 = 0.69; p < 0.01). SJ exhibited the strongest association with 100 m sprint performance, (R2 = 0.62, p < 0.01). The agility t-test did not show a significant association. The combination of the YBT ANT and SJ demonstrated a predictive capability for 100 m sprint performance (R2 = 0.67, p < 0.001). In conclusion, this study revealed predictive capabilities between dynamic balance, jumping ability, and 100 m sprint performance in sprinters with intellectual disabilities.